A Decade in the MIST: Learnings from Investigations of Drug Metabolites in Drug Development under the “Metabolites in Safety Testing” Regulatory Guidance - Schadt, Simone; Bister, Bojan; Chowdhury, Swapan K.; Funk, Christoph; Hop, Cornelis E.C.A.; Humphreys, W. Griffith; Igarashi, Fumihiko; James, Alexander D.; Kagan, Mark; Khojasteh, S. Cyrus; Nedderman, Angus N.R.; Prakash, Chandra; et al. (Drug metabolism and disposition, 2018)
Since the introduction of metabolites in safety testing (MIST) guidance by the Food and Drug Administration in 2008, major changes have occurred in the experimental methods for the identification and quantification of metabolites, ways to evaluate coverage of metabolites, and the timing of critical clinical and nonclinical studies to generate this information. In this cross-industry review, we discuss how the increased focus on human drug metabolites and their potential contribution to safety and drug-drug interactions has influenced the approaches taken by industry for the identification and quantitation of human drug metabolites. Before the MIST guidance was issued, the method of choice for generating comprehensive metabolite profile was radio chromatography. The MIST guidance increased the focus on human drug metabolites and their potential contribution to safety and drug-drug interactions and led to changes in the practices of drug metabolism scientists. In addition, the guidance suggested that human metabolism studies should also be accelerated, which has led to more frequent determination of human metabolite profiles from multiple ascending-dose clinical studies. Generating a comprehensive and quantitative profile of human metabolites has become a more urgent task. Together with technological advances, these events have led to a general shift of focus toward earlier human metabolism studies using high-resolution mass spectrometry and to a reduction in animal radiolabel absorption/distribution/metabolism/excretion studies. The changes induced by the MIST guidance are highlighted by six case studies included herein, reflecting different stages of implementation of the MIST guidance within the pharmaceutical industry.